2005
DOI: 10.1002/eqe.501
|View full text |Cite
|
Sign up to set email alerts
|

Shaking table tests on reinforced concrete frames without and with passive control systems

Abstract: An extensive experimental program of shaking table tests on reduced-scale structural models was carried out within the activities of the MANSIDE project, for the development of new seismic isolation and energy dissipation devices based on Shape Memory Alloys (SMAs). The aim of the experimental program was to compare the behaviour of structures endowed with innovative SMA-based devices to the behaviour of conventional structures and of structures endowed with currently used passive control systems.\ud This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(111 citation statements)
references
References 12 publications
1
110
0
Order By: Relevance
“…FAST capacity curve is evaluated in the hypothesis of attainment of a soft-storey plastic mechanism in the building at its first storey (e.g., Dolce et al 2005). This capacity curve can be defined in the acceleration displacement response spectrum (ADRS) format (S a -S d ) through the definition of four parameters (see also De Luca et al 2013a;Manfredi et al 2013):…”
Section: Capacity Curve and Idamentioning
confidence: 99%
“…FAST capacity curve is evaluated in the hypothesis of attainment of a soft-storey plastic mechanism in the building at its first storey (e.g., Dolce et al 2005). This capacity curve can be defined in the acceleration displacement response spectrum (ADRS) format (S a -S d ) through the definition of four parameters (see also De Luca et al 2013a;Manfredi et al 2013):…”
Section: Capacity Curve and Idamentioning
confidence: 99%
“…In fact, in the case of existing buildings (not capacity designed), column-sway storey collapse mechanisms are likely to occur, especially if infills are present, due to their relatively high strength contribution compared with RC structural elements. In particular, for uniformly infilled RC buildings, the strength contribution of infill elements leads to an approximately uniform distribution of storey shear strength along the height of the building; thus, damage is concentrated at the first storey, where the shear demand is higher (Dolce et al, 2005). The subsequent drop in strength, caused by the brittle nature of infills, finally leads to the development of a soft storey ductile mechanism, with a residual strength mainly provided by RC columns at ground level.…”
Section:  mentioning
confidence: 99%
“…The self-centering and energy-dissipating capabilities of superelastic SMAs make these materials advantageous in seismic response control of structures. For example, Dolce et al (2005) validated the benefits of SMA-incorporated base isolations in controlling structural and non-structural damage of RC frames. Padgett et al (2010) tested SMA restrainer cables on a four-span large-scale concrete bridge.…”
Section: Introductionmentioning
confidence: 95%
“…Studies on SMA-based seismic response modification devices were reported by Grasser and Cozzarelli (1991), Aiken et al (1993), Whittaker et al (1995), Clark et al (1995), Dolce et al (2000), DesRoches et al (2004), Dolce et al (2005), McCormick et al (2006), Zhu and Zhang (2007a), Li et al (2008), Casciati et al (2009), Padgett et al (2010), Yang et al (2010), Liu et al (2011), and several other researchers. The self-centering and energy-dissipating capabilities of superelastic SMAs make these materials advantageous in seismic response control of structures.…”
Section: Introductionmentioning
confidence: 98%